Using Geospatial Technology in the Preliminary Analysis in a Competive Field Setting. - Grubb, Tracey; Zellmer, Alison (My University, 2009)
Military Geography is the study of spatial aspects, both man made and natural which a ect the planning, conduct, and aftermath of military operations. A fall 2008 military geography class was divided up into two teams and conducted a paint ball capture the flag exercise as part of a semester research project. The study area was approximately 500 acres and a combination of both forest and some outer areas of farmland. There was also a combination of both higher elevation and low-lying flood plains within the forest. The purpose of this exercise was to become familiar with navigation techniques and geospatial equipment in a realistic application.
Color poster with text, images, charts, and maps.
Keywords: Military geography; War games--Maps; Geospatial data; Posters